Elevated IgG Responses in Infants Are Associated With Reduced Prevalence of Mycobacterium tuberculosis Infection - Logan, Erin; Luabeya, Angelique Kany Kany; Mulenga, Humphrey; Mrdjen, Dunja; Ontong, Cynthia; Cunningham, Adam F.; Tameris, Michele; McShane, Helen; Scriba, Thomas J.; Horsnell, William G. C.; Hatherill, Mark (Frontiers in Immunology, 2018)
Background It is unclear whether antibodies can prevent Mycobacterium tuberculosis (Mtb) infection. In this study, we examined the relationship between total plasma IgG levels, IgG elicited by childhood vaccines and soil-transmitted helminths, and Mtb infection prevalence, defined by positive QuantiFERON (QFT) test. Methods We studied 100 Mtb uninfected infants, aged 4–6 months. Ten infants (10%) converted to positive QFT test (QFT+) within 2 years of follow-up for Mtb infection. Antibody responses in plasma samples acquired at baseline and tuberculosis investigation were analyzed by enzyme-linked immunosorbent assay and ImmunoCAP® assay. Results QFT− infants displayed a significant increase in total IgG titers when re-tested, compared to IgG titers at baseline, which was not observed in QFT+ infants. Bacille Calmette-Guérin (BCG) vaccine-specific IgG2 and live-attenuated measles vaccine-specific IgG were raised in QFT− infants, and infants who acquired an Mtb infection did not appear to launch a BCG-specific IgG2 response. IgG titers against the endemic helminth Ascaris lumbricoides increased from baseline to QFT re-testing in all infants. Conclusion These data show raised IgG associates with a QFT-status. Importantly, this effect was also associated with a trend showing raised IgG titers to BCG and measles vaccine. Our data suggest a possible protective association between raised antibody titers and acquisition of Mtb infection, potentially mediated by exposure to antigens both related and unrelated to Mtb.